Efficacy of ECT in severe obsessive-compulsive disorder with Parkinson’s disease - Gadit, Amin Muhammad (BMJ Publishing Group, 2012)
A man in his 60’s was admitted following a serious suicide attempt secondary to severe obsession with bowel movements and severe depression. He had multiple previous admissions with similar presentations and responded partially to psychotropic medications. It was transpired that obsessive compulsive disorder preceded depression and being overwhelmed with this obsession related to bowel movement, he decided to end his life. Electro-convulsive therapy was commenced with good results. His obsessive-compulsive disorder came under control to a greater extent and there was an improvement in his mood.